ANALYSIS OF FACTORS AFFECTING CELLULAR BUSINESS INCOME IN SUKABUMI CITY 2019 - Danang Wijayanto Wijayanto; Yohanes Jhony Kurniawan; Hariyatno Hariyatno Hariyatno (Universitas Indraprasta PGRI Jakarta, 2021)
This research was conducted to determine the influence of mobile phone sales, sales of credit vouchers and sales of handphone accessories to the revenue of cellular entrepreneurs in the City of Sukabumi. Data collection in research carried out by interview, observation and literature study. Test equipment used with multiple regression analysis, regression coefficient analysis, coefficient of determination with testing partial and simultaneous testing. This study used quantitative research methods aimed at testing predetermined hypotheses. The sample used in this study amounted to 40 respondents. Analysis of the data used is the multiple regression analysis test and the classic assumption test. From the results of the significance test, there is a significant simultaneous influence (together) of the variables of mobile phone sales, sales of credit vouchers and sales handphone accessories to the revenue of cellular entrepreneurs. While based on partial testing, there is a significant influence of mobile phone sales, sales of credit vouchers and sales of handphone accessories to the revenue of cellular entrepreneurs. And the order of variable contribution that influences the revenue of cellular entrepreneurs is the variable of sales of the credit vouchers, sales of handphone accessories and mobile phone sales.